2020
DOI: 10.1101/2020.07.22.215814
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Selective targeting of non-centrosomal AURKA functions through use of a targeted protein degradation tool

Abstract: Targeted protein degradation tools are becoming a new therapeutic modality, allowing small molecule ligands to be reformulated as heterobifunctional molecules (referred to as ‘PROTACs’, for PROteolysis Targeting Chimeras) that recruit a ubiquitin ligase to the target of interest, leading to ubiquitination of the target and its destruction via the ubiquitin-proteasome system. A number of PROTACs against targets of clinical interest have been described, but detailed descriptions of the cell biology modulated by … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 64 publications
1
4
0
Order By: Relevance
“…This half-life is consistent with recent kinetic studies on PROTAC kinetics (Figure 3 E-G). 34,35,39,40 In addition, these three studies demonstrate sensitivity of timescales to enzyme concentration, bifunctional molecule dose and target affinities (Figure 3E-G), providing further support for the validity of our mathematical model. Critically, this ~3 hour time-scale is 16x faster than the than the typical rate of protein turnover (~48 hours, Figure 4b) 42 which explains why PROTAC's can exhibit efficacy even with modest binding affinities (Kd ~ 1µM).…”
Section: Timescale Of Synthetic Molecule Mediated Ternary-catalysissupporting
confidence: 60%
“…This half-life is consistent with recent kinetic studies on PROTAC kinetics (Figure 3 E-G). 34,35,39,40 In addition, these three studies demonstrate sensitivity of timescales to enzyme concentration, bifunctional molecule dose and target affinities (Figure 3E-G), providing further support for the validity of our mathematical model. Critically, this ~3 hour time-scale is 16x faster than the than the typical rate of protein turnover (~48 hours, Figure 4b) 42 which explains why PROTAC's can exhibit efficacy even with modest binding affinities (Kd ~ 1µM).…”
Section: Timescale Of Synthetic Molecule Mediated Ternary-catalysissupporting
confidence: 60%
“…IC50 values for NanoBRET were taken from biological replicates and were expressed in µM. Values higher than 30 Interestingly, despite all parent compounds have been published to strongly bind WDR5, the JW series did not form detectable binary complexes in cells, but they showed weak interaction in lysed cells. The weak interaction of these PROTACs was intriguing based on the published activity of these PROTACs as potent WDR5 degraders.…”
Section: Detection Of Binary Complexesmentioning
confidence: 99%
“…IC50 values for NanoBRET were taken from biological replicates and were expressed in µM. Values higher than 30 Assessment of the binary complexes provided interesting insights into the mechanism of the tested PROTACs. Regardless the sub 10 µM binding affinity in lysed cells towards VHL and WDR5, affinities in intact cells were significantly lower possibly due to poor membrane penetration of the used PROTACs.…”
Section: Detection Of Binary Complexesmentioning
confidence: 99%
“…Among the limited tests performed to date, one group has found that an AURKA-targeting PROTAC preferentially binds and degrades spindle-associated AURKA at a higher rate than centrosomal AURKA, suggesting that PROTACs could be fine-tuned to target a specific pool of AURKA. 161 To date, there are no studies that investigate the usage of an AURKA targeting PROTAC in a clinical trial.…”
Section: Inhibitors Of Aurora Kinases: Preclinical Studiesmentioning
confidence: 99%
“…PROTACs contain 2 binding moieties that connect the endogenous ubiquitin ligase pathway to targeted proteins to cause their degradation and sometimes have greater activity than agents such as kinase inhibitors, particularly if a kinase has noncatalytic roles (e.g., scaffolding complexes). Among the limited tests performed to date, one group has found that an AURKA-targeting PROTAC preferentially binds and degrades spindle-associated AURKA at a higher rate than centrosomal AURKA, suggesting that PROTACs could be fine-tuned to target a specific pool of AURKA 161 . To date, there are no studies that investigate the usage of an AURKA targeting PROTAC in a clinical trial.…”
Section: Inhibitors Of Aurora Kinases: Preclinical Studiesmentioning
confidence: 99%